Acupuncture or Acupressure at the Sanyinjiao (SP6) Acupoint for the Treatment of Primary Dysmenorrhea: A Meta-Analysis - Chen, Ma-Na (Hindawi Publishing Corporation, 2013)
This meta-analysis aimed to evaluate the effectiveness of acupuncture or acupressure at the Sanyinjiao (SP6) acupoint in relieving pain associated with primary dysmenorrhea. We searched the scientific literature databases to identify randomized controlled trials. The primary outcome was visual analogue scale (VAS) pain score. Three acupuncture and four acupressure trials were included in the meta-analyses. For the acupuncture analysis, there was no difference in the mean VAS score reduction between the SP6 acupoint and control (GB39 acupoint) groups (−4.935; lower limit = −15.757, upper limit = 5.887; P = 0.371). For the acupressure analysis, there was a significant difference in the mean VAS score after intervention between the SP6 acupoint and control (rest/light touch at SP6/nonacupoint acupressure) groups, favoring the SP6 acupoint group (−1.011; lower limit = −1.622, upper limit = −0.400; P = 0.001). Sensitivity analyses demonstrated good reliability of the meta-analyses findings. These findings suggest that acupuncture at SP6 is not more effective than acupuncture at an unrelated acupoint in the relief from primary dysmenorrhea. Acupressure at SP6 may be effective in the relief from primary dysmenorrhea. High-quality randomized controlled trials are needed to confirm these findings.